2014
DOI: 10.1371/journal.pone.0088594
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid Type 1 Receptors Transiently Silence Glutamatergic Nerve Terminals of Cultured Cerebellar Granule Cells

Abstract: Cannabinoid receptors are the most abundant G protein-coupled receptors in the brain and they mediate retrograde short-term inhibition of neurotransmitter release, as well as long-term depression of synaptic transmission at many excitatory synapses. The induction of presynaptically silent synapses is a means of modulating synaptic strength, which is important for synaptic plasticity. Persistent activation of cannabinoid type 1 receptors (CB1Rs) mutes GABAergic terminals, although it is unclear if CB1Rs can als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 73 publications
(109 reference statements)
4
22
0
2
Order By: Relevance
“…), allowing the net exocytosis to be estimated and providing a measure of the size of the recycling pool (Ramirez‐Franco et al . ).…”
Section: Resultsmentioning
confidence: 97%
“…), allowing the net exocytosis to be estimated and providing a measure of the size of the recycling pool (Ramirez‐Franco et al . ).…”
Section: Resultsmentioning
confidence: 97%
“…Retrograde suppression of GABA release will profoundly influence neural activity and release of neuromodulators, which may then affect synaptic integration and plasticity of post-synaptic processes. For instance, prolonged stimulation using a cannabinoid agonist, HU-210 in cerebellar granule cells induces silencing of CB1r and mutes GABA-containing axon terminals (Ramirez-Franco et al, 2014). To unequivocally establish such a cellular interaction, a triple immunolabeling using immunoperoxidase and dual immunogold labeling approach (Reyes et al, 2011; Reyes et al, 2012b; Kravets et al, 2013) may be carried out in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…The localization of DGL- in various brain regions also indicates putative interactions with other neurotransmitters/neuropeptides. Widespread function of CB1r modulation involves inhibition of neurotransmitter release (Freund et al, 2003; Chevaleyre et al, 2006; Garkun and Maffei 2014; Kury et al, 2014; Ramirez-Franco et al, 2014), while cannabinoid-induced neurotransmitter release has also been demonstrated in various brain regions (Tzavara et al, 2001; Tzavara et al, 2003; Oropeza et al, 2005; Muntoni et al, 2006; Page et al, 2008; Kirilly et al, 2013). Initially, the mechanism proposed for eCB release involved a depolarization-induced event followed by retrograde signaling and binding of the endogenous ligand to presynaptically distributed receptors (Piomelli, 2003; Chevaleyre et al, 2006; Castillo et al, 2012; Wang and Lupica, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Further inquiry into the precise mechanism revealed that PKA inhibitors had no effect on EPSC generation, while the EPAC-specific activator increased EPSC levels, supporting the importance of EPAC as a major regulator in synaptic vesicle release (490). Additionally, EPAC activation could prevent presynaptic silencing, as well as accelerate awakening, of axonal terminals after prolonged cannabinoid type 1 receptor stimulation, while PKA modulation was ineffective (852). Furthermore, EPAC-null animals display decreased EPSC generation and spontaneous activation in neurons of the hippocampus (1155).…”
Section: Synaptic Neurotransmissionmentioning
confidence: 94%
“…Moreover, cAMP-potentiated fusion events in the first phase of glucose-induced exocytosis were markedly abridged in EPAC2 Ϫ/Ϫ mice (957 A similar signalosome is also observed for EPAC2 in the CNS during neurotransmitter release, which is but another form of exocytosis employed by neurons to rapidly communicate throughout the body. EPAC is observed to be a major regulator in presynaptic terminal release probability of synaptic vesicles (490,852,897). This is accomplished through a signalosome where EPAC2 binds Rim1␣, increasing association with Rab3 to maneuver synaptic vesicles in closer proximity to the plasma membrane (300,301).…”
Section: Epac2 Signalosomes At Insulin-secreting Granules and Synaptimentioning
confidence: 99%